Spontaneous Emission of an Excited Atom in a Dusty Unmagnetized Plasma Medium - Naser Alinejad; Noushin Pishbin (Advances in Materials Science and Engineering)
Investigation of spontaneous decay of an excited atom in dusty unmagnetized plasma is presented in this paper. The transverse contribution to the decay rate is normally associated with spontaneous emission. The rate of spontaneous emission can be obtained by Fermi’s golden rule. In this calculation, the transverse contribution to dielectric permittivity and Green function technique are used. Calculation of the decay rate of atoms is applicable to understand the particular structure of the vacuum state of the electromagnetic field.